Status of patient safety culture in Arab countries: a systematic review - Elmontsri, Mustafa (BMJ Open, 2017)
OBJECTIVES: To explore the status of patient safety culture in Arab countries based on the findings of the Hospital Survey on Patient Safety Culture (HSPSC). DESIGN: Systematic review. METHODS: We performed electronic searches of the MEDLINE, EMBASE, CINAHL, ProQuest and PsychINFO, Google Scholar and PubMed databases, with manual searches of bibliographies of included articles and key journals. We included studies that were conducted in the Arab countries that were focused on patient safety culture. 2 reviewers independently verified that the studies met the inclusion criteria and critically assessed the quality of the studies. RESULTS: 18 studies met our inclusion criteria. The review identified that non-punitive response to error is seen as a serious issue which needs to be improved. Healthcare professionals in the Arab countries tend to think that a ‘culture of blame’ still exists that prevents them from reporting incidents. We found an overall similarity between the reported composite score for dimension of teamwork within units in all of the reviewed studies. Teamwork within units was found to be better than teamwork across hospital units. All of the reviewed studies reported that organisational learning and continuous improvement was satisfactory as the average score of this dimension for all studies was 73.2%. Moreover, the review found that communication openness seems to be a concerning issue for healthcare professionals in the Arab countries. CONCLUSIONS: There is a need to promote patient safety culture as a strategy for improving the patient safety in the Arab world. Improving patient safety culture should include all stakeholders, like policymakers, healthcare providers and those responsible for medical education. This review was limited only to English language publications. The varied settings in which the HSPSC was used may have influenced the areas of strengths and weaknesses as healthcare workers' perception of safety culture may differ.